2008
DOI: 10.1007/s00128-008-9505-7
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Sequence of Toxic Inorganic Anions on a Soil

Abstract: The adsorption of six anions (arsenate(As(V)), chromate(Cr(VI)), fluoride(F(-I)), molybdate(Mo(VI)), selenate(Se(VI)), and selenite(Se(IV))) on an andosol and the concomitant H(+) consumptions together with the sorption were investigated to understand the behaviors of toxic inorganic anions in environment. Based on the estimated adsorption maximum by the simple Langmuir equation, the order of adsorption affinity to the andosol at a suspension pH of 5.0 was F(-I) > > phosphate(P(V)) > Se(IV) > Mo(VI) >or= As(V)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…The sum of chromate released in the two desorption processes reached over 50% in both soils (Table 2). This desorption is in accordance with the higher affinity of phosphate for iron oxides and soil surfaces compared with chromate [41,85].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The sum of chromate released in the two desorption processes reached over 50% in both soils (Table 2). This desorption is in accordance with the higher affinity of phosphate for iron oxides and soil surfaces compared with chromate [41,85].…”
Section: Discussionsupporting
confidence: 81%
“…According to Jiang et al [40], both specific adsorption and electrostatic adsorption contribute to chromate adsorption by variable-charge soils (Ferralsols, Acrisol). Saeki [85] reported that chromate is adsorbed by a Silandic Andosol forming outer-sphere complex.…”
Section: Discussionmentioning
confidence: 99%
“…This process may drive the release of adsorbed As(V) in groundwater since As(III) has a lower sorption capacity than As(V) on Fe(III) hydroxides at circumneutral pH values. Production of sulfide may also induce sulfide-driven arsenic mobilization from arsenopyrite and black shale pyrite Cumming et al 1999;Langner and Inskeep 2000;Oremland and Stolz 2003;Zhu et al 2008 Natural organic matter (NOM) may induce arsenic release by competing for adsorption sites, forming aqueous complexes, changing the redox potential of surface adsorption sites Wang and Mulligan 2006 Anion exchange with competitive ions such as phosphate, carbonate and possibly some anionic organic compounds Meng et al 2002;William et al 2003;Saeki 2008;Zhang et al 2005;Tao et al 2006 pH increase in semiarid or arid environments to values [8.5 as a result of the combined effects of mineral weathering and high evaporation rates leads to desorption of adsorbed As [mainly As(V)] and other anions (V, B, F, Mo, Se and U) from mineral oxides; need for irrigation in semiarid regions may also drive As mobilization Smedley and Kinniburgh 2002;Nickson et al 2005;Madhavan and Subramanian 2007;Busbee et al 2009 As mobilization by the formation of arsenocarbonate complexes, suggested by strong correlation between As and HCO 3 -; the latter correlation may also be an indirect result of the microbial mediated reduction of Fe(III) hydroxides, which produces both the As and HCO 3 -species Kim et al2000;Anawar et al 2004;Radu et al 2005 Groundwater age and aging of Fe oxides leading to more ordered forms such as goethite and hematite that have larger crystal sizes and reduced surface areas may lead to a release of As adsorbed on young Fe oxides Cornell and Schwertmann 1996;Dixit and Hering 2003;Pedersen et al 2006;Radloff et al 2007 Lake in Northern Latium, Central Italy. The samples were weathered on the surface and they were brushed and polished before using them in the leaching tests to minimize the effect of external deposits.…”
Section: As Mobilization Triggers In Aquifers Referencementioning
confidence: 99%